Design of an Underactuated End-effector for an Apple Picking Robot - Li Xiang; Yu Jinghu (Jixie chuandong)
A practical type of underactuated three- fingered end- effector for an apple picking robot is proposed,the end- effector structure is designed and the 3D modeling is completed by using the Unigraphics NX. Through designing the structure of multi- phalanges finger and tendon rope,the purpose of improving the flexibility of mechanism grasping is achieved. Based on the movement principle of finger grasping motion,the relationship between the tendon rope force and the joint torque is analyzed. Under the constraint condition of ultimate load that cannot damage the surface of apples,the key component torsional spring is designed and the structural parameters of the torsional spring are determined with the goal of achieving reliability and flexibility of the mechanism motion. The flexibility and applicability of the mechanism are effectively improved. The end-effector is also suitable for other globular or different sizes of fruit and it has certain applicability to grab.